The Influence of Tax Rates and Tax Service Quality on Vehicle Taxpayer Compliance Motorcycle in West Ilir, Palembang City - Ladewi, Yuhanis (Accounting and Business Journal, 2021)
This research was conducted to answer the problems, namely how was the influence of tax rates and the quality of motor vehicle tax services on motor vehicle tax payers compliance in Ilir Barat, Palembang. The aim was to determine the influence of taxes rates and the quality of motor vehicle tax services on motor vehicle tax payers compliance in Ilir Barat, Palembang. The type of this research used was an associative and descriptive research. The research was conducted in the Ilir Barat, Palembang. The variables used were tax rates, quality of tax services and taxpayer compliance. The data used was primary data. Data collection techniques used in this study were questionnaires.The data analysis techniques used were descriptive statistics and inferential statistics. Inferential statistical analysis consists of the classical assumption test, multiple linear regression analysis, the coefficient of determination test and then proceeded with the hypothesis test (t test). Data analysis was computed by the Statistical Program for Special Science (SPSS). The results of data analysis showed that tax rates and the quality of tax services had influence on motor vehicle taxpayer compliance in Ilir Barat, Palembang.